2022
DOI: 10.1177/10775463221147156
|View full text |Cite
|
Sign up to set email alerts
|

Fault diagnosis method of wheel diameter difference based on stacked autoencoder and multiple kernel learning

Abstract: Tread wear rates of the right and left wheels of a wheelset are not the same because of the complexity of the track condition, which causes the wheel diameter difference (WDD). The WDD can influence vehicle dynamic performances and shorten the service life of the wheelset. To diagnose and recognize the condition of the WDD in time, a data-driven method based on multi-sensor information fusion is proposed. Different statistical features are extracted from the time and frequency domains of the axle-box accelerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…When the track random irregularity changes greatly, the impulse signal appears for the wheelset with the WDD. The influence can be noted more easily for the larger WDD [21]. So, the subband with a bigger SESGI can be selected for the fault diagnosis of the WDD.…”
Section: The Proposed Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…When the track random irregularity changes greatly, the impulse signal appears for the wheelset with the WDD. The influence can be noted more easily for the larger WDD [21]. So, the subband with a bigger SESGI can be selected for the fault diagnosis of the WDD.…”
Section: The Proposed Methodsmentioning
confidence: 99%
“…For all subbands, the sequence of RMS and SESGI can be expressed as [R 1 , R 2 ,…, R j ] and [S 1 , S 2 ,…, S j ] respectively. The standard deviation of the sequence is used to generate the weight of RMS or SESGI, and the new fusion index FI can be defined according to equation (21). It can be found that FI can be considered as a compromise between the energy factor and the impulse factor.…”
Section: The Proposed Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a key component in urban rail vehicles, once the axle-box bearing fails, it will lead to several accidents and even impact the operation safety of vehicles (Yu et al, 2022a). Axle-box bearings are the most frequently damaged component in urban rail vehicles (Zhang et al, 2022; Yu et al, 2022b; Sui et al, 2022). In accordance, it is urgent to improve the dynamic performance of axle-box bearings, such as nice stability, small vibration, and long service life.…”
Section: Introductionmentioning
confidence: 99%